EFFECT OF BALINESE FLUTE INSTRUMENT FOR IMPROVING COGNITIVE FUNCTION IN ELDERLY - Laksmidewi, Anak Agung Ayu Putri; Tertia, Clarissa; Indah, Carolin Tiara Lestari; Suherlim, Richard; Arshinta, Lasta; Mahadewi, Ni Putu Ayu Putri (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Cognitive impairment is mostly affected the elderly population which reduces the quality of life for sufferers and their families. The last research showed that listening to Balinese flute instrument music increased cognitive function, especially in the memory domain. However, the study is still limited to small populations. Objective: to determine whether playing the Balinese flute with or without listening to the